Understanding Spatiotemporal Station and Trip Activity Patterns in the Lisbon Bike-Sharing System - Albuquerque, Vitória (2022)
Albuquerque, V., Andrade, F., Ferreira, J. C., & Dias, M. S. (2021). Understanding Spatiotemporal Station and Trip Activity Patterns in the Lisbon Bike-Sharing System. In A. L. Martins, J. C. Ferreira, A. Kocian, & V. Costa (Eds.), Intelligent Transport Systems, From Research and Development to the Market Uptake: 4th EAI International Conference, INTSYS 2020, Proceedings (pp. 16-34). (Lecture Notes of the Institute for Computer Sciences, Social-Informatics and Telecommunications Engineering, LNICST; Vol. 364 LNICST). Springer Science and Business Media Deutschland GmbH. https://doi.org/10.1007/978-3-030-71454-3_2